(untitled) (International Journal of Food and Nutritional Sciences, 2019)
Brain tumor identification is really challenging task in early stages of life. But now, it became advanced with various machine learning and deep learning algorithms. Nowadays, brain tumor automatic identification is of great interest. To detect the brain tumor, the MRI images of patient’s are used.